PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA SEKOLAH (APBS) TERHADAP BUDGETARY SLACK DENGAN MOTIVASI DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL PEMODERASI - Yuliastuti, Yuriah; Prabowo, Muhammad Agung (Paradigma, 2015)
The research design is survey and quantitative approach. Hypotheses that proposed is (1) a high budgetary participation will have positive effect on budgetary slack, (2) a high motivation will have negative effect on the relationship between budgetary participation with budgetary slack (3) a high organizational commitment will have negative effect on the relationship between budgetary participation with budgetary slack.Respondents are school budgetary team Â involved school budgeting (APBS) in educational institutions of SMA and SMK located in Magetan Regency, amounted to 102 pearson. It uses the regression with the absolute residual test method to test hypothesis. The results of this research showed that the proposed third hypothesis can be accepted, meaning that (1) a high budgetary participation will have positive effect on budgetary slack, (2) a high motivation will have negative effect on the relationship between budgetary participation with budgetary slack (3) a high organizational commitment will have negative effect on the relationship between budgetary participation with budgetary slackKeywords: budgetary participation, motivation, organizational commitment, slack budgetary